Determination of the postprandial cut-off value of triglyceride after a daily meal corresponding to fasting optimal triglyceride level in Chinese subjects - Xie, Yingying; Guo, Liling; Chen, Hao; Xu, Jin; Qu, Peiliu; Zhu, Liyuan; Tan, Yangrong; Zhang, Miao; Wen, Tie; Liu, Ling (Frontiers in Nutrition, 2023)
Background According to the 2021 consensus statement about triglyceride (TG)-rich lipoproteins and their remnants from the European Atherosclerosis Society (EAS), fasting TG level < 1.2 mmol/L is regarded as optimal, otherwise considered as non-optimal TG (NoTG). However, the postprandial cut-off value after a daily meal corresponding to a fasting TG level of 1.2 mmol/L has not been explored. Materials and methods Six hundred and eighteen inpatients aged 18 to 70 were recruited in this study. Among them, 219 subjects had fasting TG levels < 1.2 mmol/L (i.e., OTG group), and 399 subjects had fasting TG levels ≥ 1.2 mmol/L (i.e., NoTG group). Serum levels of blood lipids, including calculated non-high-density lipoprotein cholesterol (non-HDL-C) and remnant cholesterol (RC), were monitored at 0, 2, and 4 h after a daily Chinese breakfast according to their dietary habits. Receiver operating characteristic (ROC) curve analysis was used to determine the postprandial cut-off value corresponding to the fasting TG level of 1.2 mmol/L. Kappa statistics were performed to determine the consistency between fasting and postprandial cut-off values in determining whether TG was optimal. Univariate and multivariate logistic regression analyses were conducted to evaluate the associations between NoTG and potential confounders. Subgroup analyses were performed to explore the association between postprandial TG levels at 4h (pTG4h) and NoTG in greater detail. Results Postprandial levels of TG and RC significantly elevated and peaked at 4h after a daily breakfast in two groups (P < 0.05). The optimal cut-off value at 4h corresponding to fasting TG of 1.2 mmol/L was 1.56 mmol/L. According to the fasting cut-off value, the percentage of patients with NoTG was 64.6% in the fasting state while increasing obviously to 73.3–78.4% at 2 and 4h, respectively, after a daily Chinese breakfast. According to the postprandial cut-off value, the percentage of patients with NoTG at 4h after a daily Chinese breakfast was 62.6% which was close to 64.6% in the fasting state. The Kappa coefficient was 0.551, indicating a moderate consistency between the fasting and postprandial cut-off values in the diagnosis of NoTG. Moreover, the subjects with NoTG determined by the postprandial TG cut-off value had an obviously higher postprandial level of RC (1.2 vs. 0.8 mmol/L) and percentage of HRC (37.1 vs. 32.1%) than those determined by the fasting TG cut-off value. Multivariate logistic regression analyses demonstrated that except for BMI, pTG4h emerged as an independent predictor of not. Subgroup analyses revealed that the association between pTG4h and NoTG was consistent across subgroups. Conclusion Taken together, we for the first time determined TG 1.56 mmol/L as the postprandial cut-off value corresponding to fasting TG 1.2 mmol/L in Chinese subjects. This could make it more convenient to determine whether TG is optimal or not in the fasting or postprandial state.